Hubungan Dukungan Keluarga dengan Kebahagiaan pada Lanjut Usia yang Tinggal di Kelurahan PB Selayang I - Widya Dwi Handayani; Azhar Aziz; Arif Fachrian (Universitas Medan Area, 2026)
This study aimed to examine the relationship between family support and happiness among older adults in PB Selayang I Village. This study employed a quantitative approach with a correlational design. The population consisted of 116 older adults living in PB Selayang I Village, with a sample of 36 older adults selected using purposive sampling. Data were collected using family support and happiness scales based on a Likert-type response format. The data were analyzed using the Product Moment correlation technique. The descriptive analysis showed that family support was categorized as high, while happiness was also categorized as high. The hypothesis testing indicated that the research hypothesis was supported, demonstrating a positive relationship between family support and happiness among older adults in PB Selayang I Village. This finding indicates that higher levels of family support are associated with higher levels of happiness among older adults. The findings highlight the importance of family support in fostering positive psychological well-being among older adults.